Snow white and other fairy tales - Kelly; Miles (Essex Miles Kelly Publishing Ltd, 2015)
The Brothers Grimm Snow-white and other stories is a beautifully illustrated storybook for children aged 5+. Containing four famous favourites by master storytellers the Brothers Grimm, young readers will discover a world of imagination and adventure within. This book has a stunning sparkly cover, making it an ideal gift for fairy tale fans. Stories included: Snow-white and the Seven Dwarfs, The Gold Children, The Valiant Little Tailor, The Little Folks' Presents.